Chemical Characterization of Instant Powder Based on Dutch Eggplant Peel and Seed Waste Using the Foam Drying Method - Fahmi Arifan; Wisnu Broto; Oktaviani Kusuma Wardani; Siti Fatimah (Diponegoro University, 2022)
Chemical content of Dutch eggplant shell waste and seeds Each 500 mL extract contains sugar (0.46), crude fiber (1.98), vitamin C (0.0716), anthocyanin (122.57) and pH (5.9) . Where with some of the ingredients contained in the skin and seeds of Dutch eggplant skin waste and seeds, it can be processed into an instant powder drink that is beneficial to the health of the human body, one of which is preventing free radicals and treating hypertension. This study aims to determine the formulation and specifications of instant drink powder made from waste skins and seeds from waste Dutch eggplant shells and seeds using the foam drying method and the addition of sucrose as a sweetener. In this study the experiments used RAL with 2 times in a row and variable sucrose concentration (10%; 15%; 20%), stirring time (30 minutes; 45 minutes; 1 hour) and a comparison of air and eggplant. (1:1; 1:2; 1:3) In this study the vitamin C test, organoleptic test and fiber test were analyzed. So the result is that the best vitamin test is obtained by adding 10% sucrose with an absorbance value of 0.303. the level of preference of the organoleptic panelists on the variable addition of 20% sucrose and for the highest fiber content was around 30% on the variable addition of 20% sucrose.